2021
DOI: 10.21203/rs.3.rs-481805/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High nerve density in breast cancer is associated with poor patient outcome

Abstract: Background: Active crosstalk between the nervous system and breast cancer cells as well as other cell types within the tumour microenvironment has been experimentally demonstrated in vitro and in animal models. However, low frequencies of peripheral nerve presence in human breast cancers reported in previous studies (~30% of cases) potentially negate a major role of the nervous system in breast cancer development and progression. This study aimed to better define the incidence of nerves within human breast can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In breast tumors, the presence of tyrosine hydroxylase‐positive immunoreactivity was demonstrated, both in tumor and in nontumor stromal areas (Kamiya et al, 2019; Szpunar et al, 2016). Their density varies widely between studies (D. Li et al, 2021; Szpunar et al, 2016) what suggests that catecholamine synthesis within the tumor may be a dynamic process and vary according to the progression stage of breast cancer, being higher in early tumor growth (Szpunar et al, 2016). This pattern was demonstrated by Mercedes and colleagues (Szpunar et al, 2016), who showed that in MMTV‐PyMT mice, a model that closely mimics clinical breast cancer stages, the sympathetic nerve fibers innervation was higher in early premalignant masses comparatively to that observed in later‐stage adenocarcinomas.…”
Section: The Adrenergic System In the Breast Tumor Microenvironmentmentioning
confidence: 99%
“…In breast tumors, the presence of tyrosine hydroxylase‐positive immunoreactivity was demonstrated, both in tumor and in nontumor stromal areas (Kamiya et al, 2019; Szpunar et al, 2016). Their density varies widely between studies (D. Li et al, 2021; Szpunar et al, 2016) what suggests that catecholamine synthesis within the tumor may be a dynamic process and vary according to the progression stage of breast cancer, being higher in early tumor growth (Szpunar et al, 2016). This pattern was demonstrated by Mercedes and colleagues (Szpunar et al, 2016), who showed that in MMTV‐PyMT mice, a model that closely mimics clinical breast cancer stages, the sympathetic nerve fibers innervation was higher in early premalignant masses comparatively to that observed in later‐stage adenocarcinomas.…”
Section: The Adrenergic System In the Breast Tumor Microenvironmentmentioning
confidence: 99%